Analysis of Thermal Elastohydronamic Lubrication of Inclined Double-roller Enveloping Hourglass Worm Drive - Ou Yue; Li Jinkuan; Zhu Yan; Liu Zaixin; Liao Honghui (Jixie chuandong)
To improve the lubrication performance,anti-scuffing capacity and efficiency of enveloping worm,the elastohydrodynamic lubrication（ EHL） line contact model is established based on the research of meshing performance of inclined double-roller enveloping hourglass worm drive and the theory of EHL. According to the line contact mathematical model with Ree-Eyring fluid,the distribution of the minimum film thickness of EHL and thermal EHL（ TEHL） are analyzed. The roller radius,offset distance,orifice coefficient and inclined angler,which impacted the lubrication performance of this worm drive are analyzed. The analysis results indicate that the inclined double-roller enveloping hourglass worm drive has better lubrication performance,the roller radius and orifice coefficient have the biggest impact on TEHL. In order to keep good lubrication performance of this worm drive,the roller radius should be not too large,the offset distance and orifice coefficient are not too small.